A New Species of Aporia (Lepidoptera: Pieridae) from Northwest Yunnan, China with Taxonomic Notes on Its Similar Sympatric Taxa - Hu, Shao-Ji; Zhang, Hui-Hong; Yang, Yang (Zootaxa, 2021)
The northwest corner of Yunnan Province, China is the world-class diversity centre of the genus Aporia Hübner, 1819 (Lepidoptera: Pieridae). During our expeditions to this area in 2019 and 2020, a new species of Aporia was discovered from the upper Yangtze River valley in northwest Yunnan, China. The new taxon, A. chunhaoi sp. nov., is similar to A. lhamo (Oberthür, 1893) but can be easily identified by larger size, much paler (creamy) male hindwing, as well as different genitalic structures. Our field surveys and comparative studies also confirmed a new range of A. lhamo in the upper Yangtze River valley, and the morphological variation of this species is discussed herein.